2012
DOI: 10.1371/journal.pone.0046732
|View full text |Cite
|
Sign up to set email alerts
|

Improved Methods of Carnivore Faecal Sample Preservation, DNA Extraction and Quantification for Accurate Genotyping of Wild Tigers

Abstract: BackgroundNon-invasively collected samples allow a variety of genetic studies on endangered and elusive species. However due to low amplification success and high genotyping error rates fewer samples can be identified up to the individual level. Number of PCRs needed to obtain reliable genotypes also noticeably increase.MethodsWe developed a quantitative PCR assay to measure and grade amplifiable nuclear DNA in feline faecal extracts. We determined DNA degradation in experimentally aged faecal samples and test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
29
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 19 publications
2
29
0
1
Order By: Relevance
“…Two buffers (GUS lysis buffer and RNAlater) worked well in the few studies that tested them however; this needs to be investigated further. Reddy et al (2012) found that the amount of amplifiable DNA in faeces declined with time. This is probably because environmental conditions (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Two buffers (GUS lysis buffer and RNAlater) worked well in the few studies that tested them however; this needs to be investigated further. Reddy et al (2012) found that the amount of amplifiable DNA in faeces declined with time. This is probably because environmental conditions (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Each of the twenty-three samples were preserved in the three different media (n=69); 95% ethanol, ASL buffer (Qiagen) and Two-step storage (ethanol and silica beads; e.g. Wasser et al, 1997;Reddy et al, 2012). Wherever a sample was encountered a small portion from the outer part of the faeces (c.f.…”
Section: Faecal Samplingmentioning
confidence: 99%
See 2 more Smart Citations
“…Oliveira e Duarte (2013) reportam um sucesso de amplificação de 45%, mas nenhuma amostra, de um total de 52, foi identificada. Michalski et al (2011) (REDDY et al, 2012;DEMAY et al, 2014 ) Vários fatores influenciam no sucesso de amplificação, sendo a degradação do DNA e a inibição por PCR os principais empecilhos ao lidar com amostras não invasivas (BEJA-PEREIRA et al, 2009). Condições climáticas favoráveis e o correto armazenamento, aparentemente, melhoram os resultados pela menor degradação ocorrida nessas situações (NSUBUGA et al, 2004;BRINKMAN et al, 2010).…”
Section: Discussionunclassified